Exercise Attenuates Intermittent Hypoxia-Induced Cardiac Fibrosis Associated with Sodium-Hydrogen Exchanger-1 in Rats - Chen, Tsung-I; Tu, Wei-Chia (Frontiers in Physiology, 2016)
Purpose: To investigate the role of sodium–hydrogen exchanger-1 (NHE-1) and exercise training on intermittent hypoxia-induced cardiac fibrosis in obstructive sleep apnea (OSA), using an animal model mimicking the intermittent hypoxia of OSA. Methods: Eight-week-old male Sprague–Dawley rats were randomly assigned to control (CON), intermittent hypoxia (IH), exercise (EXE) or IH combined with exercise (IHEXE) groups. These groups were randomly assigned to subgroups receiving either a vehicle or the NHE-1 inhibitor cariporide. The EXE and IHEXE rats underwent exercise training on an animal treadmill for 10 weeks (5 days/week, 60 minutes/day, 24–30 m/minute, 2–10% grade). The IH and IHEXE rats were exposed to 14 days of IH (30 seconds of hypoxia - nadir of 2-6% O2 - followed by 45 seconds of normoxia) for 8 hours/day. At the end of 10 weeks, rats were sacrificed and then hearts were removed to determine the myocardial levels of fibrosis index, oxidative stress, antioxidant capacity and NHE-1 activation. Results: Compared to the CON rats, IH induced higher cardiac fibrosis, lower myocardial catalase and superoxidative dismutase activities, higher myocardial lipid and protein peroxidation and higher NHE-1 activation (p < 0.05 for each), which were all abolished by cariporide. Compared to the IH rats, lower cardiac fibrosis, higher myocardial antioxidant capacity, lower myocardial lipid and protein peroxidation and lower NHE-1 activation were found in the IHEXE rats (p < 0.05 for each). Conclusion: IH-induced cardiac fibrosis was associated with NHE-1 hyperactivity. However, exercise training and cariporide exerted an inhibitory effect to prevent myocardial NHE-1 hyperactivity, which contributed to reduced IH-induced cardiac fibrosis. Therefore, NHE-1 plays a critical role in the effect of exercise on IH-induced increased cardiac fibrosis.